Cardiac Changes in Acute Ischemic Stroke - إحسان منى; أكرم جحجاح; عيسى لايقة (Latakia University Journal -Medical Sciences Series, 2024)
Introduction and Purpose: Acute ischemic stroke has an effect on electrocardiography results, cardiac enzyme levels and echocardiography Our primary objective is to study the electrocardiographic changes and troponin level in patients with acute acute ishemic stroke and to study the effect of the severity and location of the infarction on these changes. Materials and Methods: This study was performed between February 2021 and February 2022, included 178 Acute ischemic stroke patients admitted within 24 hours of symptom onset. Electrocardiogram, Echocardiography and troponinI test were performed within 72 hours. Results: 18 patients (10.1%) had an ejection fraction less than 50%, 44 patients (24.7%) had positive troponin. 41 patients (23%) had ischemic changes in ECG, 36 patients (20.2%) had QTc prolongation, and 36 patients (20.2%) had arrhythmias. The mean systolic blood pressure at admission was higher in left-sided stroke (176.76±37.6 (VS 138.30 ± 21.3) (p value 0.0001) .It was also higher in moderate and severe stroke (p value 0.03). Sinus tachycardia was more frequent in left-sided stroke (p value0.01) while sinus bradycardia was more frequent in right-sided stroke (p value0.01).Systolic dysfunction was more frequent in anterior circulation strokes (P value 0.04) These findings support the importance of the adjunctive role of cardiac monitoring strategies in acute ischemic stroke.